Mineralocorticoid Receptor Signaling as a Therapeutic Target for Renal and Cardiac Fibrosis - Tesch, Greg H.; Young, Morag J. (Frontiers in Pharmacology, 2017)
Activation of the mineralocorticoid receptor (MR) plays important roles in both physiological and pathological events. Blockade of MR signaling with MR antagonists has been used clinically to treat kidney and cardiac disease associated with hypertension and other chronic diseases, resulting in suppression of fibrosis in these organs. However, the current use of steroidal MR antagonists has been limited by off target effects on other hormone receptors or adverse effects on kidney tubular function. In this review, we summarise recent insights into the profibrotic roles of MR signaling in kidney and cardiovascular disease. We review experimental in vitro data identifying the pathological mechanisms associated with MR signaling in cell types found in the kidney (mesangial cells, podocytes, tubular cells, macrophages, interstitial fibroblasts) and heart (cardiomyocytes, endothelial cells, vascular smooth muscle cells, macrophages). In addition, we demonstrate the in vivo importance of MR signaling in specific kidney and cardiac cell types by reporting the outcomes of cell type selective MR gene deletion in animal models of kidney and cardiac disease and comparing these findings to those obtained with MR antagonist treatment. This review also includes a discussion of the potential benefits of novel non-steroidal MR antagonists for targeting kidney and cardiac fibrosis compared to existing steroidal MR antagonists, as well as the possibility of novel combination therapies and cell selective delivery of MR antagonists.